2021
DOI: 10.3390/ma14205983
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Structure and Properties of Lightweight Cement Composite with PVA Fibers

Abstract: This study addresses the application of polyvinyl alcohol (PVA) fibers to improve the performance of lightweight cement composites with pozzolans. Blended cement mixes based on expanded glass granules were modified with PVA fibers (Type A: Ø40 µm, L = 8 mm and Type B: Ø200 µm, L = 12 mm). The following research methods were used to analyse the effect of the fibers on the structure of cement matrix and physical-mechanical properties of lightweight composite: SEM, XRD, DTG, calorimetry tests, and standard test m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The reason behind this behavior is related to the properties of PVA fibers which have a higher modulus of elasticity compared to that of PP fibers which leads to a reduction in the creep strain. This behavior conforms with the results of Donatas et al [19], who stated that PVA fibers own a high modulus of elasticity and may reduce the crack width, hence reducing the creep strain of the mix. Results displayed that a denser layer of hydration products was formed around the PVA fibers and the amount of the formed portlandite and C-S-H gel was higher around the PVA fibers, Fig.…”
Section: Ecc Microstructural Behavior When Using Polymer Fiberssupporting
confidence: 92%
“…The reason behind this behavior is related to the properties of PVA fibers which have a higher modulus of elasticity compared to that of PP fibers which leads to a reduction in the creep strain. This behavior conforms with the results of Donatas et al [19], who stated that PVA fibers own a high modulus of elasticity and may reduce the crack width, hence reducing the creep strain of the mix. Results displayed that a denser layer of hydration products was formed around the PVA fibers and the amount of the formed portlandite and C-S-H gel was higher around the PVA fibers, Fig.…”
Section: Ecc Microstructural Behavior When Using Polymer Fiberssupporting
confidence: 92%
“…The foam concrete produced after optimization shows fine cracks on the surface ( Figure 11 a), indicating the foam concrete has poor cracking resistance. The PVA fibers have good affinity with cement-based cementitious materials [ 39 ], and in order to ensure the integrity of foam concrete, the PVA fibers with high elastic modulus are incorporated to improve the cracking resistance. The compressive-flexural strength ratio is an important index to characterize the flexibility of foam concrete, which can well reflect the cracking resistance of foam concrete.…”
Section: Resultsmentioning
confidence: 99%
“…Adeyemi et al [12] determined that the 2% PVA fber content is adequate to prevent any cracks resulting from shrinkage in ECC mixtures. Donatas et al [13] revealed that PVA fbers that have high modulus of elasticity may decrease the crack width and consequently reduce the drying shrinkage. Sara Saed et al [14] displayed that the use of two types of Portland limestone cement, Karasta (CK) and Tasluja (CT) PLC, leads to a reduction in drying shrinkage and creep due to the chemical composition of the two types of the cement and the calcium carbonate percent added to the clinker; therefore, less clinker/cement ratio gives lower creep and shrinkage.…”
Section: Introductionmentioning
confidence: 99%